PENGARUH KEBIJAKAN PPKM TAHAP II JAWA TENGAH TERHADAP MOBILITAS PENDUDUK PADA SEKTOR RETAIL DAN REKREASI - Nuari Priambudi, Bagus; Ariani, Nofa Martina; Wijaya, Muhammad Indra Hadi; Pradana, Brian (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
The mobility of urban populations towards potential sectors is one form of economic activity turnover. However, this condition is currently disrupted due to Covid-19. This condition occurs almost all over the world, not least Indonesia. To suppress the rapid spread of the outbreak, several policies were issued in order to reduce the mobility of the high population. This article aims to find out the influence of the implementation of PPKM Phase II policy on Population Mobility in the retail and leisure sectors. This article uses a library study approach by processing google mobility report data, so that the correlation to variables tested is known. PPKM Central Java Phase II policy can affect the mobility of the population towards the retail and leisure sectors. The existence of this policy, indirectly limits the space of community activities in making movements.